2021
DOI: 10.1021/acscatal.1c00275
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Stabilized Azo-anion Radical in Dehydrogenative Synthesis of N-Heterocycles. An Exclusively Ligand Centered Redox Controlled Approach

Abstract: Herein we report an exclusively ligand-centered redox controlled approach for the dehydrogenation of a variety of N-heterocycles using a Zn­(II)-stabilized azo-anion radical complex as the catalyst. A simple, easy-to-prepare, and bench-stable Zn­(II)-complex (1b) featuring the tridentate arylazo pincer, 2-((4-chlorophenyl)­diazenyl)-1,10-phenanthroline, in the presence of zinc-dust, undergoes reduction to form the azo-anion radical species [1b]− which efficiently dehydrogenates various saturated N-heterocycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 76 publications
2
35
0
Order By: Relevance
“…Control experiments revealed that the reaction begins with forming the single-electron reduced azo-anion radical species [ 1a ] − , which has been earlier identified in an analogous study . It is hypothesized that an alkoxide ligand forms an adduct with this radical anionic metal complex by simultaneously replacing the Cl – ligand to generate the catalytically active species, A , emphasizing the crucial role of the base t BuOK in facilitating deprotonation of the alcohol (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Control experiments revealed that the reaction begins with forming the single-electron reduced azo-anion radical species [ 1a ] − , which has been earlier identified in an analogous study . It is hypothesized that an alkoxide ligand forms an adduct with this radical anionic metal complex by simultaneously replacing the Cl – ligand to generate the catalytically active species, A , emphasizing the crucial role of the base t BuOK in facilitating deprotonation of the alcohol (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 80%
“… , To further ensure the hydrazo species, when 2j-D 2 was dehydrogenated stoichiometrically under optimized conditions, characteristic N–D stretching frequencies were observed at 2063 and 2116 cm –1 . , The deuterium labeling experiment confirms that the hydrogen/deuterium atoms removed during the dehydrogenation of 2j and 2j-D 2 are stored in the azo-chromophore. Analysis of the IR spectrum of the stoichiometric reaction of 1a , 3j , and 2j-D 2 , however, exhibits both N–H and N–D stretching at 3028, 3062 and 2085, 2113 cm –1 , respectively. , The ability of the electrochemically generated two-electron reduced hydrazo species [ 1a ] 2– to catalyze the conversion of benzophenone imine ( 6u′ ) to N -benzhydrylpyridin-2-amine ( 6u ) in the presence of 2j further confirms the active participation of the hydrazo species (see SI). Deuterium labeling experiment with 2-aminopyridine ( 3j ) and diphenylmethanol 2j-D 2 resulted in 25%-deuterium-incorporated N -alkylated amine product 6u-D (Scheme , entry 6).…”
Section: Results and Discussionmentioning
confidence: 84%
“…During the past decades, great progresses have been made for the synthesis of quinazoline derivatives (Scheme 1, a ). The traditional methods for such N ‐heterocycles are the condensation reactions of 2‐(aminomethyl)aniline and aldehydes/alcohols/nitriles in a combination of transition metal‐catalysts (such as Cu‐, Ni‐, Ir‐, Ru‐, Mn‐, and Zn‐complex) and oxidants [10–15] . Recently, quinazolines could be obtained efficiently under metal‐free conditions [16–21] .…”
Section: Figurementioning
confidence: 99%
“…The traditional methods for such Nheterocycles are the condensation reactions of 2-(aminomethyl)aniline and aldehydes/alcohols/nitriles in a combination of transition metal-catalysts (such as Cu-, Ni-, Ir-, Ru-, Mn-, and Zn-complex) and oxidants. [10][11][12][13][14][15] Recently, quinazolines could be obtained efficiently under metal-free conditions. [16][17][18][19][20][21] Further-more, the synthesis of corresponding quinazoline derivatives by organocatalytic protocols has been reported.…”
mentioning
confidence: 99%
“…[1] The CÀ N bond formation reaction and the direct synthesis of various nitrogen-containing heterocyclic compounds through the construction of CÀ N bonds have been fully studied and widely used in synthetic chemistry. [2] Since the 1960s, palladium, copper, iron and other transition metals [3][4][5][6][7][8][9][10][11] catalyzed the CÀ N bond coupling has become an important method for the synthesis of nitrogen heterocyclic compounds. With the continuous development of green synthesis, metalfree catalyzed CÀ N bond formation become the trend of modern synthesis.…”
Section: Introductionmentioning
confidence: 99%